1978
DOI: 10.3109/15563657808988248
|View full text |Cite
|
Sign up to set email alerts
|

Blood Cadmium Level and Hypertension in Humans

Abstract: Blood cadmium level was determined in 29 nontreated hypertensive male subjects and 29 controls. All were individually matched for sex, age, and smoking habits. No differences were found between hypertensives (3.3 +/- 0.4 ng/ml) and normotensives (2.6 +/- 0.4 ng/ml).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

1980
1980
1991
1991

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…However, other investigations into this relationship have yielded negative findings (e.g. Dally et al, 1978), and a recent review of this topic by Bousquet ( 1979) notes that the human studies must be considered as only suggestive of the possibility of a causal connection between cadmium and hypertension.…”
Section: Human Cardiovascular Systemmentioning
confidence: 94%
“…However, other investigations into this relationship have yielded negative findings (e.g. Dally et al, 1978), and a recent review of this topic by Bousquet ( 1979) notes that the human studies must be considered as only suggestive of the possibility of a causal connection between cadmium and hypertension.…”
Section: Human Cardiovascular Systemmentioning
confidence: 94%
“…There are controversies as to wheth er Cd causes hypertension either clinically or experimentally. There is evidence for [Schroeder, 1965;Mackenzie and Kay, 1973;Glauser et al, 1976] and against [Beevers et al, 1976;Ostergaard, 1977;Dally et al, 1978] as far as clinical reports are concerned. When Cd is fed to rats orally, both positive [Schroeder and Buckman, 1967;Kanisawa and Schroeder, 1969;Perry et al, 1977Perry et al, , 1979Petering et al, 1979;Fadloun and Leach, 1980] and negative [Lener and Bibr, 1971;Doyle et al, 1975;Eakin et al, 1980] pressure effects have been reported.…”
Section: Introductionmentioning
confidence: 99%
“…Man y of the investigations empl oyed a "quasi case-referent" design in which sick persons (with hypertension or IHD) were compa red to health y referents (77,123,124,128,130,133,(140)(141)(142)(144)(145)(146)(147)(148)(149)(150)(151)(152)(153)(154). The se studies are called " quas i case-re ferent" becau se in reali ty they ar e crosssectional studies in which " disease" (hypertension , for exampl e) is measured simulta neously with " exposure" (for example, cadmium in blood).…”
Section: Cadmiummentioning
confidence: 99%
“…One o f the wor st problems concerns the measurem ent of cadm ium exposure. Man y studies estimated the exposure by measur ing cadmium in blood (77,80,124,137,138,140,141,(148)(149)(150)(151)153). The blood cadmium level is, however, not a very reliable mea sure of the cadmium body burden.…”
Section: Cadmiummentioning
confidence: 99%